Effect of sulfasalazine on endothelium-dependent vascular response by the activation of Nrf2 signalling pathway - Sonmez, Muhammed Ikbal; Shahzadi, Andleeb; Kose, Cagla; Sonmez, Haktan; Ozyazgan, Sibel; Akkan, Ahmet Gokhan (Frontiers in Pharmacology, 2022)
Background: Diabetes mellitus leads to endothelial dysfunction and accumulation of oxygen radicals. Sulfasalazine-induced Nrf2 activation reduces oxidative stress in vessels. Thus, in the present study we investigated the effects of sulfasalazine on endothelial dysfunction induced by high glucose we also elucidated the underlying mechanism involved in glucose-induced endothelial dysfunction. Methods: For this experiment we used rat aorta to calculate the dose response curve of noradrenalin and acetylcholine. Vessels were incubated in normal and high glucose (44mM) for two hours. To investigate glucose and sulfasalazine effects the vessels of the high glucose group were pre-treated with sulfasalazine, JNK inhibitor (SP600125), and ERK inhibitor (U0126) for 30 minutes. The eNOS, TAS, TOS, and HO-1 levels were estimated by commercially available ELISA kits. Results: In the high glucose group, the E max for contraction was significantly higher (p <0.001), than the E max for relaxation. These functional changes were parallel with the low levels of eNOS (p <0.05). High glucose vessel treated with sulfasalazine showed low E max value for contraction (p <0.001) however, the E max for relaxation was significantly high (p <0.001). In the JNK group, E max for contraction and relaxation was inhibited (p <0.001) compared to sulfasalazine treated vessels. HO – 1 enzyme levels were significantly low (p <0.01) with sulfasalazine but higher with ERK inhibitor (p <0.05). Conclusion: High glucose induced endothelial dysfunction and sulfasalazine reduced damage in high glucose vessels by activating eNOS, antioxidant effect, and particularly inducing Nrf2 via the ERK and JNK pathways.